Government Investiment and Quality Spaces: An opportunity for the Greater ABC Paulista? - Moro Junior, Enio (National Journal of City Management, 2025)
Objective – This reflection aims to demonstrate, specifically based on the Greater ABC Paulista region—a southeastern subregion of the São Paulo Metropolitan Area—the low quality of public investment in urbanism, which contrasts with the effective existence of resources, pressing needs, and administrative obstacles to improving public actions that prioritize urban spaces. Methodology – The investigation of this topic is based on the perceptible observation of the low quality of public spaces in the Greater ABC Paulista, despite the region presenting excellent economic and social indicators. In this context, the strategy for understanding the issue involved analyzing municipal public investments in urbanism through the budgets of the cities studied, extraconstitutional federal transfers, and wealth production in the region. Originality / Relevance – The Greater ABC Paulista, a subregion of the São Paulo Metropolitan Area (RMSP), historically driven by the industrial expansion of the 20th century, has economic and social indicators that are relatively favorable compared to national averages. However, this wealth is not translated into public spaces of urbanistic and architectural quality. Public investment in urbanism is fragmented, of low quality, and yields limited returns. Results – The region lacks a long-term urban agenda and remains stagnant in models from the 1960s that prioritize individual plots over the city as a whole. The capture of federal resources, in addition to constitutionally mandatory funds, is modest and hindered by a complex bureaucratic system developed by the Government Executive Management (GIGOV) and Caixa Econômica Federal, resulting in significant resources being invested in proposals of low quality and effectiveness. Theoretical/Methodological Contributions – The Brazilian federal pact, particularly after the 1988 Constitution, continues to concentrate decision-making power over territory-structuring public investments in the central government. This article questions this model, while disagreeing with an exclusive emphasis on local government protagonism, and suggests the need to discuss a new, more fluid model of investment between central power and regional structures. Social and Environmental Contributions – Revising the framework of public investment in urbanism, from its most comprehensive perspective, enables a more qualified discussion on joint actions among different levels of government and effectively brings urbanism to a leading role in the production of cities with more equitable and sustainable territories.